Optimization of integrated bee agro-tourism marketing system at KTH Pasir Madu Ciparigi village, Sukadana district, Ciamis regency - Faruk, Mujaddid; Romansyah, Romdah; Firdaus, Hendra (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
The purpose of the Community Service (PKM)